2020
DOI: 10.1186/s43045-020-00074-5
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and behavioral problems of 9–18-year-old girls and its relationship to menarche age

Abstract: Background Adolescence is associated with rapid changes in behavioral patterns which affect the functioning of the person in adulthood. The purpose of this research was to study the emotional and behavioral problems of 9–18-year-old girls and their relationship to menarche age. This cross-sectional study was done on girls aged 9–18 years old in Shiraz city. A cluster sampling method was used to select about 2000 students in 2015. Then, a questionnaire including demographic characteristics and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…City, Iran, which reported that the most prevalent emotional-behavioural problems among adolescents were emotional symptoms (Tayebi et al, 2020). The age of menarche was significantly associated with emotional and behavioural difficulties.…”
Section: Behavior Changes Of Menarche Students and The Teacher And Sc...mentioning
confidence: 96%
“…City, Iran, which reported that the most prevalent emotional-behavioural problems among adolescents were emotional symptoms (Tayebi et al, 2020). The age of menarche was significantly associated with emotional and behavioural difficulties.…”
Section: Behavior Changes Of Menarche Students and The Teacher And Sc...mentioning
confidence: 96%
“…Menurut WHO pengolongan umur 10-19 tahun merupakan usia remaja. Sebagian besar sikap dan perilaku akan terbentuk pada masa remaja ini seperti menentukan kebiasaan gaya hidup, dan kesehatan pada masa dewasa 17 .…”
Section: Pembahasanunclassified
“…Adolescence is a progression from youth to adulthood accompanied by numerous developmental changes which can affect adulthood functioning in the later stages of life (Tayebi et al, 2020). Adolescence is characterised by maximum physiological changes and psychosocial developments (McDade et al, 2011).…”
Section: Introductionmentioning
confidence: 99%